1995
DOI: 10.1083/jcb.129.3.659
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of membranes involved in excitation-contraction coupling of cardiac muscle.

Abstract: Abstract. Peripheral couplings are junctions between the sarcoplasmic reticulum (SR) and the surface membrane (SM). Feet occupy the SR/SM junctional gap and are identified as the SR calcium release channels, or ryanodine receptors (RyRs). In cardiac muscle, the activation of RyRs during excitation-contraction (e-c) coupling is initiated by surface membrane depolarization, followed by the opening of surface membrane calcium channels, the dihydropyridine receptors (DHPRs). We have studied the disposition of DHPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 48 publications
(60 reference statements)
6
178
0
1
Order By: Relevance
“…Complex (q~) charging waveforms appear specifically to occur in skeletal muscle in which excitation-contraction coupling may involve direct allosteric interactions between DHPR-voltage sensors and RyR-Ca 2+ release channels (for review see Huang, 1993). In contrast, the Ca 2+ channel gating currents that also initiate elevations of cytosolic Ca 2+ in arthropod skeletal muscle and mammalian cardiac muscle are simple monotonic decays whose associated charge nevertheless also exhibits steep steady-state voltage dependences similar to those of the q~ system (Gilly and Scheuer, 1984;Bean and Rios, 1989) these latter systems may be indirectly activated by a triggering entry of extracellular Ca 2 rather than through such direct receptor-receptor couplings (Beuckelman and Wier, 1988;Fabiato, 1985;Sun et al, 1995). The question then arises whether the complex qv kinetics in skeletal muscle specifically reflect allosteric interactions between the molecules that initiate excitationcontraction coupling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex (q~) charging waveforms appear specifically to occur in skeletal muscle in which excitation-contraction coupling may involve direct allosteric interactions between DHPR-voltage sensors and RyR-Ca 2+ release channels (for review see Huang, 1993). In contrast, the Ca 2+ channel gating currents that also initiate elevations of cytosolic Ca 2+ in arthropod skeletal muscle and mammalian cardiac muscle are simple monotonic decays whose associated charge nevertheless also exhibits steep steady-state voltage dependences similar to those of the q~ system (Gilly and Scheuer, 1984;Bean and Rios, 1989) these latter systems may be indirectly activated by a triggering entry of extracellular Ca 2 rather than through such direct receptor-receptor couplings (Beuckelman and Wier, 1988;Fabiato, 1985;Sun et al, 1995). The question then arises whether the complex qv kinetics in skeletal muscle specifically reflect allosteric interactions between the molecules that initiate excitationcontraction coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent biochemical evidence (Anderson and Meissner, 1995) suggests that DHPRs are linked allosterically to RyR-I or the RyR~ isoforms in mammalian or amphibian skeletal muscle triads, respectively (Olivares et al, 1991), but not to the RyR-II isofonns in cardiac muscle (Sun et al, 1995). Such a scheme would still permit DHPRs to generate a steadystate q~ charge transfer driven by transverse tubular potential (cf.…”
Section: I_ O Omentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies in chicken developing peripheral couplings have shown that there is a very close relationship between the size of arrays of feet in the SR and the area covered by DHPR in the junctional portion of the sarcolemma (25). While DHPRs are clearly clustered closely to RyRs, freeze-fracture studies have shown no evidence of organization of DHPRs into tetrads (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). DHPRs are randomly clustered in junctional domains of exterior membranes and no spatial relationship with feet was detected ( Figure 3, A and C, and Figure 5, B and D).…”
Section: Dhpr and Ryr Interact Differently In Skeletal And Cardiac Mumentioning
confidence: 99%
“…The possible reason for this alternate tetrad/RyR1 association will be further discussed in section 6. In cardiac muscle, immunohistochemistry experiments and morphological studies have shown that DHPRs are also clustered in close correspondence with RyR domains (7,14). Indeed, studies in chicken developing peripheral couplings have shown that there is a very close relationship between the size of arrays of feet in the SR and the area covered by DHPR in the junctional portion of the sarcolemma (25).…”
Section: Dhpr and Ryr Interact Differently In Skeletal And Cardiac Mumentioning
confidence: 99%